50 secrets of Surry Hills & Redfern. - Cousens, Graham; Bodey, Michael; Ho, Hilbert (Surry Hills, NSW : Bourke Street Public School P&C, 2019)
A rollicking ride through the history of Sydney's oldest and most dynamic suburbs, Surry Hills and Redfern. Follow the map or create your own tour with these colourful secrets. Imagine the way the region was and fill in the gaps on how the suburbs came to be what they are today. What secrets hide in the streets of your neighbourhood?
Title from cover.
Sheet contains map of Surry Hills and Redfern, marked with locations mentioned in this book.
In slipcase.
Includes bibliographical references (page 106)
Keywords: Surry Hills (N.S.W.) -- History -- Anecdotes; Redfern (N.S.W.) -- History -- Anecdotes; Surry Hills (N.S.W.) -- Guidebooks; Redfern (N.S.W.) -- Guidebooks; Aboriginal and/or Torres Strait Islander content; Australian history; Australian